Konsep Ta’dib Syed Muhammad Naquib Al-Attas dan Relevansinya dengan Pendidikan Karakter - Ida Mariana; Purniadi Putra; Jaelani (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
This research departs from the phenomenon of the moral crisis that is happening now, which has spread to children, youth, parents and society in general. Therefore, character education is so important, because character education is also moral and etiquette education. If moral and adab education has been implemented, it will form good and noble human beings. According to Syed Muhammad Naquib Al-attas Among the basic educational concepts of Al-Attas is the concept of ta'dib. For him, the fundamental problem in Islamic education is the loss of adab values in a broad sense. This is more due to the ambiguity in understanding the concepts of tarbiyah, ta'lim, and ta'dib. Al-Attas tends to use the term ta'dib for the concept of Islamic education because if the concept of ta'dib is applied comprehensively, integrally and systematically in the practice of Islamic education, it is hoped that various human resource development problems can be overcome. An even more basic reason is adab which is closely related to knowledge, because knowledge cannot be taught or disseminated to students unless a teacher has the right adab towards knowledge in various fields.